2022
DOI: 10.1037/ser0000594
|View full text |Cite
|
Sign up to set email alerts
|

Promoting resilience in persons with serious mental health conditions during the Coronavirus pandemic.

Abstract: This article highlights the profound and far-reaching impact of the Coronavirus disease 2019 health crisis on persons with serious mental health conditions. To understand and mitigate against the negative effects of the crisis on this population, we offer a resilience intervention framework that attends to three key resilience processes, namely control, coherence, and connectedness (3Cs). We then detail interventions and associated evidence-informed intervention strategies at the individual, interpersonal, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…These findings are consistent with research conducted by Friis-Healy et al [ 11 ], which indicated that in the context of this public health crisis, resilience often accompanies adaptive emotional responses. To provide clinicians with more tools to bolster resilience in their client populations, Friis-Healy et al provided a resilience-based intervention framework grounded in the “3Cs” approach to understanding the key tenets of resilience in coping with traumatic stress: control, coherence, and connectedness [ 11 ]. We adopt this framework to help explain the resilient nature of the NYS COVID-19 Emotional Support Helpline and the caller–agent interaction that arose from this community-based intervention.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings are consistent with research conducted by Friis-Healy et al [ 11 ], which indicated that in the context of this public health crisis, resilience often accompanies adaptive emotional responses. To provide clinicians with more tools to bolster resilience in their client populations, Friis-Healy et al provided a resilience-based intervention framework grounded in the “3Cs” approach to understanding the key tenets of resilience in coping with traumatic stress: control, coherence, and connectedness [ 11 ]. We adopt this framework to help explain the resilient nature of the NYS COVID-19 Emotional Support Helpline and the caller–agent interaction that arose from this community-based intervention.…”
Section: Introductionsupporting
confidence: 92%
“…Perhaps most traumatic for many survivors was the loss of closure through both the inability to say goodbye to dying family members and friends and the powerlessness to hold memorial services for those loved ones [ 10 ]. Individuals most at risk for developing PTSD symptoms may be those who had already experienced mental health concerns before the COVID-19 global pandemic and those who became seriously ill themselves or lost others to the virus [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one article, Tavel et al (2022) surveyed psychotherapists across three European countries on their level of resilience during the pandemic and found that those with higher levels of dispositional resilience reported lower levels of stress, highlighting the importance of resilience in stress management during this unique time in our history. In another article, Friis–Healy et al (2022) offer a resilience framework from which new approaches and interventions can be developed to help adults with serious mental illness build resilience during and after the COVID-19 pandemic. Two other articles in this special section examined the mental health of first responders who have been overworked and overburdened by the pandemic.…”
mentioning
confidence: 99%